Heat shock transcription factor HSF1 plays a critical role in HER2-induced cellular transformation and tumorigenesis - Meng, Le (2010)
The heat shock transcription factor HSF1 was recently demonstrated to play a key role in the development of tumors associated with activation of Ras or inactivation of p53. Here we show that HSF1 is required for cell transformation and tumorigenesis induced by HER2 oncogene responsible for aggressive breast tumors. Upon expression of HER2, untransformed human mammary epithelial cells MCF-10A underwent neoplastic transformation, formed foci in culture and tumors in nude mouse xenografts. However, expression of HER2 in MCF-10A cells with knockdown of HSF1 did not cause either foci formation or tumor growth in xenografts. The anti-tumorigenic effect of downregulation of HSF1 was associated with HER2-induced accumulation of the CDK inhibitor p21 and decrease of the mitotic regulator survivin, which resulted in growth inhibition and cell senescence. In fact, either knockout of p21 or overexpression of survivin alleviated these effects of HSF1 knockdown. Proliferation of certain human HER2-postitive breast cancer lines also requires HSF1, since its knockdown led to upregulation of p21 and/or drop of survivin, precipitating growth arrest. Similar effects were observed with a small molecular weight inhibitor of the heat shock response NZ28. Effects of HSF1 knockdown on growth arrest and senescence of HER2-expressing cells were associated with downregulation of Hsp72 and Hsp27. Therefore, HSF1 is critical for proliferation of HER2-expressing cells, most likely since it maintains levels of HSPs, which in turn control regulators of senescence p21 and survivin.